Designing Reality Fit m-Voting - Eilu, Emmanuel; Baguma, Rehema (My University, 2013)
In this paper, we examine the declining trends in voter turn-up in Uganda and other developing countries. We also look at the possibility of using ICT especially the widely used mobile phones to improve citizen participation in voting. We also assess the current citizen perception and responses towards using their mobile phones for voting. In addition we discuss political, technological, social and cultural factors that are likely to affect the use of mobile phones for voting.
Keywords: Developing Countries; Mobile Phone Voting; Demographics; Acceptance Patterns